Multifunctional resin-based nanocomposite coated proppants as propping agent with enhanced mechanical and thermal properties and scale inhibitor active adsorber - ALI ALZANAM, ALI AREF (2021)
Herein, resin-based nanocomposites coated proppants were developed to act both as propping agent and high active surface platform for scale inhibitors to be adsorbed and subsequently released. Glass bead proppant were coated with an ultra-thin layer of Polyurethane resin-based carbon nanocomposites via novel spray coating technique. Coated proppants were characterized using Field Emission Scanning Electron Microscope (FESEM) and Energy Dispersive X-Ray Analyzer (EDX). A Gas Loop System was designed and used to test proppant flowback. Further analysis, including contact angle measurement, API crush test, and thermogravimetric analysis (TGA) were conducted to examine proposed proppant wettability, strength to withstand closure stress, and thermal stability, respectively. Finally, adsorption and desorption tests were conducted to investigate the capability of the proposed resin-based nanocomposites coatings of multi-wall carbon nanotubes (MWCNTs) and graphene nanoplatelets (GNPs) reinforced polyurethane resin coated proppant (RCP) to enhance the adsorption and desorption of Diethylenetriamine Penta (DTPMP) scale inhibitor.